Genotypic variation for nitrogen-use efficiency in rapeseed-mustard - PK Barua; J Chutia; P Borah; M Barua (Journal of Oilseed Brassica, 2026)
Genetic variation for nitrogen-use efficiency (NUE) and related yield traits were assessed in 11 toria (Brassica rapa var.toria), 14 yellow sarson (Brassica rapa var. yellow sarson) and 7 Indian mustard (Brassica juncea) genotypes. Thesegenotypes were evaluated at 0 and 40 kg N ha-1 levels of nitrogen fertilization and, nitrogen-use efficiency (NUE) interms of agronomic efficiency was determined. Significant genetic variation was observed for all the traits studied. Atoria genotype TS65 produced the highest yield (9.92 q/ha) coupled with the highest NUE (17.5 kg kg-1). Highheritability was recorded for leaf nitrogen, 1000-seed weight, nitrate reductase activity (NRA), days to maturity, siliquaeper plant and seeds per siliqua. High genetic advance was recorded for siliquae number per plant, NRA, seeds per siliquaand leaf N. There was strong positive genetic correlation between seed yield and NUE, indicating the significance ofenhanced NUE for seed yield improvement.